Provenances trial of Cedrus Atlantica Manetti in North-Eastern Portugal - Bariteau, M. (2007)
Results from a trial with Atlas cedar (Cedrus atlantica Man.) provenances located in north-eastern Portugal are presented. Survival after plantation and initial height and base diameter are analysed. There are significant differences between provenances on survival and height, but not for diameter. Three Atlas cedar provenances were chosen as having the best performances for future afforestation programmes in north-eastern regions of Portugal with similar ecological conditions to the experimental area (A9111 Tikja, Algeria; Assa 30-92, Morocco; Ijar 135-90, Morocco).